2017
DOI: 10.1016/j.gloplacha.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A multistratigraphic approach to pinpoint the Permian-Triassic boundary in continental deposits: The Zechstein–Lower Buntsandstein transition in Germany

Abstract: The Central European Basin is very suitable for high-resolution multistratigraphy of Late Permian to Early Triassic continental deposits. Here, the well exposed transition of the lithostratigraphic Zechstein and Buntsandstein Groups of central Germany was studied for isotope-chemostratigraphy (δ 13 Corg, δ 13 Ccarb, δ 18 Ocarb), major-and trace-element geochemistry, magnetostratigraphy, palynology, and conchostracan biostratigraphy. The analyzed material was obtained from both classical key sections (abandoned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 95 publications
(137 reference statements)
0
16
0
Order By: Relevance
“…Particularly, the hematite depletion and the increase of Cu and Sr (and also the minor increase that seems to occur in the case of Ni) possibly denote anoxic conditions. Grey intervals with Cu enrichments, related to anoxia, are recorded in the lowermost Buntsandstein of the Central European Basin, Central Germany (Hiete et al, 2006;Scholze et al, 2017). Noteworthy, the end-Permian extinction is correlated with oceanic anoxia and acidification (Grice et al, 2005;Meyer and Kump, 2008) that influenced atmosphere (Kump et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, the hematite depletion and the increase of Cu and Sr (and also the minor increase that seems to occur in the case of Ni) possibly denote anoxic conditions. Grey intervals with Cu enrichments, related to anoxia, are recorded in the lowermost Buntsandstein of the Central European Basin, Central Germany (Hiete et al, 2006;Scholze et al, 2017). Noteworthy, the end-Permian extinction is correlated with oceanic anoxia and acidification (Grice et al, 2005;Meyer and Kump, 2008) that influenced atmosphere (Kump et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Copper is generally related to environments with low oxygen levels (Hofmann et al, 2000;Hiete et al, 2006;Scholze et al, 2017), which could be linked to the decrease of hematite observed by XRD. This mineral is formed in oxic conditions, and therefore the observed hematite reduction may be a consequence of lower atmospheric oxygen levels (Hiete et al, 2006;Benton and Newell, 2014).…”
Section: Mineralogy and Elemental Successionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buntsandstein‐Group deposition lasted from Induan to Anisian time (earliest to early Middle Triassic; 252 to 247 Ma; Szulc, ; Scholze et al ., ). Stratigraphic subdivision is based on basin‐wide large‐scale fining‐upward cycles (Fig.…”
Section: Geological Settingmentioning
confidence: 97%
“…14), ex clud ing the val ues of short-term pos i tive ex cur sions of this iso to pic ra tio (Horacek et al, 2007a). Al most all re ported val ues of d 13 C from Buntsandstein oo lites from the Cen tral Euro pean Ba sin show very nar row ranges be tween +1 and -4‰ (Korte and Kozur, 2005;Becker, 2007;Weidlich, 2007;Scholze et al, 2017;Fig. 14).…”
Section: Microfacies Mineralogy and Geochemistry Of The Oolitic Limementioning
confidence: 99%